Analysis of Faecal Sludge Treatment Alternatives to Enhance the Treatment Performance of Wastewater Treatment Plant (WWTP) Denpasar Sewerage Development Project (DSDP) Suwung Denpasar City - Gede Adi Wiguna Sudiartha; Prayatni Soewondo (Journal of Engineering and Technological Sciences, 2021)
Most of the wastewater generated from domestic activities in Denpasar city is treated in an off-site treatment plant located in WWTP DSDP Suwung. This includes faecal sludge that originates from on-site treatment plants. The existing treatment facilities can only treat wastewater that has a maximum biochemical oxygen demand (BOD) concentration of around 225 mg/l while the disposed faecal sludge’s BOD concentration reaches 3,394 mg/l. Therefore, an additional faecal sludge treatment plant needs to be established in order to separate the solid phase from the liquid phase. According to the treatment performance calculation, some alternative treatments can achieve BOD5 and TSS removal of up to 97% and 98% respectively. The selection of the alternative treatment was decided from weighting results of several aspects, such as economic, land use, technological and environmental aspects. The weighting method that was used in this research was Simple Additive Weighting (SAW). The advantage of SAW is its ability to do the assessment highly precisely because it is based on predetermined criteria and preference weights. Based on the weighting result, the treatment technology selected was a Solid Separation Chamber as primary treatment, combined with an Anaerobic Baffled Reactor as a secondary treatment. A Belt Filter-Press was applied to reshape the sludge into a recyclable cake. The required cost is approximately 16 billion rupiahs.